Heightened risks of cardiovascular disease in South Asian populations: causes and consequences. (3rd April 2023) - Stefil, Maria; Bell, Jack; Calvert, Peter; Lip, Gregory YH
ABSTRACT: Introduction: South Asian individuals comprise almost a quarter of the world's population and have an excess risk of atherosclerotic cardiovascular disease (ASCVD) compared to other ethnicities. In part, this can be explained by higher prevalence, earlier onset, and suboptimal control of traditional cardiovascular risk factors, such as insulin resistance, metabolic syndrome, and dyslipidaemia. However, there remains a significant residual excess risk associated with South Asian ethnicity after controlling for traditional risk factors. Areas covered: In this review, we describe the epidemiology of ASCVD in both native and diaspora South Asian populations. We explore how traditional cardiovascular risk factors, novel cardiovascular risk factors, and social determinants of health may contribute to the excess ASCVD risk seen in South Asian populations. Expert opinion: There should be increased awareness of the relative importance of South Asian ethnicity and related social determinants of health, as risk factors for ASCVD. Systematic screening processes should be tailored to this population, and modifiable risk factors should be treated aggressively. Further research is required to quantify determinants of the excess ASCVD risk seen in South Asian populations and to develop targeted interventions to address these factors.